Righteousness in Ayya Vaikundar’s Akilathirattu - D, Vaikunda Kannan (International Research Journal of Tamil, 2022)
South India has been enriched with all all kind of resources. Ayya Vaikundar’s work Akilathirattu says that the people who lived in south lived happily with Godly thoughts. The people did charitable deeds with the virtue of morals and the idea of attaining virtue, wealth, and pleasure at home. They lived happily and because of the people’s observance of the three types of righteousness, all the devas prayed to the Lord that rain should be showered. The people who ruled the country ruled as simple and strong. He considered the country people as his people. The kings did good to the people and collected very low taxes. As the king ruled well, the wealth of the people increased and the memory of Shiva remained unchanged. People lived self-disciplined among themselves. One of the most important aspects of human life is the relationship of husband and wife. Women cherished their husbands more than their life and were proud of their commitment to chastity. Women are very genuine and realized that it was wrong to talk about their love life to God. Through this article, we can learn that those who follow the three principles will lead a good life.